2010
DOI: 10.1111/j.1475-4932.2010.00667.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Economic Crises: The Great Depression and the 2008 Recession

Abstract: Economic crises, involving large and persistent declines in output and employment, are puzzles, particularly in developed countries with economies that typically function at a high level. This article analyses the Great Depression and the 2008 recession using recent developments in business cycle diagnostic procedures, and finds that the key to both episodes is understanding labour market distortions that resulted in the marginal product of labour being much higher than the marginal rate of substitution betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…We consider two theories that can explain movements in the labor wedge. First, the most obvious interpretation for the reduction of the labor wedge should be a rise of labor or consumption taxes, as they directly a¤ect consumer's decision about the time allocation and, thus, labor supply (Ohanian, 2009). To determine whether these taxes were responsible for the deterioration of the labor wedge, we use the exercise tax as the proxy of the consumption tax.…”
Section: Understanding the Labor Wedgementioning
confidence: 99%
“…We consider two theories that can explain movements in the labor wedge. First, the most obvious interpretation for the reduction of the labor wedge should be a rise of labor or consumption taxes, as they directly a¤ect consumer's decision about the time allocation and, thus, labor supply (Ohanian, 2009). To determine whether these taxes were responsible for the deterioration of the labor wedge, we use the exercise tax as the proxy of the consumption tax.…”
Section: Understanding the Labor Wedgementioning
confidence: 99%
“…According to Gordon (1993), part of the explanation of the job puzzle in the recovery from the 1990-91 recession lies in the ebullient performance of productivity. Ohanian (2010aOhanian ( , 2010b argues that the key to understanding the 2007-09 recession and its aftermath is developing theories of labor market distortions for explaining why labor input was far below the level consistent with the marginal productivity of labor. Bernanke (2003) and Yellen (2010) conjecture that productivity gains, related also to increased workers' effort, have contributed to the slowness of the recovery of the labor market and blame the frustratingly slow rate of job creation on a paradigm shift toward boosting efficiency begun in late 1980s.…”
Section: Introductionmentioning
confidence: 99%
“…As I stressed before, the role of rising productivity and higher efficiency is consistent with many economists' reading of recent jobless recoveries. As for real wage rigidities, Ohanian (2009Ohanian ( , 2010aOhanian ( , 2010b provides compelling evidence that both in the Great Depression of the 1930s and in the recession of 2008, distortions in the labor market kept wages far above market-clearing levels. Hall (2010) argues that wage unresponsiveness to the large increase in unemployment stands as a major feature of the recent recession.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have blamed the failure of the DSGE model to predict the crisis. In fact, the crisis lasted up to 2009 due to the significant productivity declines and much smaller declines in labor input according to Ohanian (2010). In addition, his analysis indicated that the 2007-2009 recession is not well understood within current classes of economic models, including both standard real business cycle models, and perhaps surprisingly including models in which financial distress reduces economic activity.…”
Section: Introductionmentioning
confidence: 99%